Phytoplankton diversity of the Gharni Reservoir in Latur district, Maharashtra, India - Vishwas Balasaheb Sakhare; Ashvini Dnyandeo Chalak (Journal of Fisheries, 2015)
The phytoplanktonic samples were collected from the Gharni Reservoir of Latur district of Maharashtra for a period of one year, from June 2013 to May 2014. Totally 18 species of phytoplankton belonging to different taxonomic groups were identified. Among these 7 species belong to Chlorophyceae, 5 species to Cyanophyceae, 3 species to Bacillariophyceae and 3 species to Euglenophyceae. The phytoplankton productivity fluctuated seasonally and the maximum number of 560 units/liter was recorded during month of February and March and minimum number of 95 units/liter during the month of September.